No role of the third-trimester inflammatory factors in the association of gestational diabetes mellitus with postpartum cardiometabolic indicators - Xiayan Yu; Wenjing Qiang; Kexin Gong; Yidan Cao; Shuangqin Yan; Guopeng Gao; Fangbiao Tao; Beibei Zhu (BMC, 2024)
Abstract Background The influence of gestational diabetes mellitus (GDM) on postpartum cardiometabolic indicators is primarily restricted to glucose and lipid metabolism, however the indicators for liver and kidney function have been rarely explored, and the role of the third-trimester inflammatory factors in these associations has never been investigated. Methods Based on the Ma'anshan birth cohort (MABC), women with or without GDM history were selected and invited to participate in a 6-year postpartum follow-up. The fasting blood samples were collected to measure 16 comprehensive metabolic indicators during a 6-year postpartum follow-up: fasting plasma glucose (FPG), glycosylated hemoglobin (HbA1c), triglycerides (TG), total cholesterol (TC), uric acid (UA), blood urea nitrogen (BUN), serum creatinine (SCR), etc. Seven inflammatory factors, including TNF-α, IFN-γ, IL-1β, IL-6, IL-10, IL-12p70, and IL-17 A, were measured with serum samples collected during the third trimester of pregnancy. Linear regression models were used to analyze the associations between GDM and 6-year postpartum metabolic indicators, GDM and third-trimester inflammatory factors, and the third-trimester inflammatory factors and 6-year postpartum metabolic indicators. Mediating and moderating effect analyses were further performed to explore if the third-trimester inflammatory factors mediate or modify the association between GDM and postpartum cardiometabolic indicators. Results From July 2021 to August 2022, 307 participants have been followed up, with 99 women with a prior GDM history. Compared with those without GDM, individuals with a prior history of GDM had significantly elevated levels of FPG (β = 0.40, 95% CI: 0.18 to 0.62, P FDR < 0.001), HbA1c (β = 0.22, 95% CI: 0.09 to 0.34, P FDR = 0.009), TyG (β = 0.22, 95% CI: 0.07 to 0.37, P FDR = 0.024) at 6 years postpartum, and the association between GDM and SCR (β = 2.43, 95% CI: 0.02 to 4.85, P FDR = 0.144) reached nominal significance level. GDM history was associated with a decreased level of third-trimester IL-17 A (β = -0.58, 95% CI: -0.99 to -0.18, P FDR = 0.035). No significant association between third-trimester inflammatory factors and 6-year postpartum metabolic indicators was observed. And no mediating or moderating effect of third-trimester inflammatory factors was observed in those associations. Conclusion A prior history of GDM was significantly associated with elevated FPG, HbA1c, and TyG in women at 6 years postpartum, whereas third-trimester inflammatory factors had no role in mediating or moderating these associations.